Wpływ rodziny i innych grup małych na poczucie zadowolenia i bezpieczeństwa jednostki - Żurek, Aldona (Wydawnictwo Naukowe UAM, 2000)
Man can accept different strategies o f functions on the plane o f social microstructures. They are connected with the realization of individual aims or with individual obligations towards membership groups. In both cases small groups give their members support (as for example, material, time, or normative ones). Thanks to them they can intensify or weaken in different characters o f their activities. Stabilization o f family life together with participation in other small groups influences the quality o f life o f an individual, creates the standards o f participations on the institutional plane o f social life. It also decides about the creation o f the safe vision and o f friendly world.
The influence o f family and other small groups on the sense o f satisfaction and safety o f individual